The effects of perceived organizational support, perceived supervisor support and intra-organizational network resources on turnover intentions: A study of Chinese employees in multinational enterprises - Newman, A.; Thanacoody, R.; Hui, Wendy (MCB University Press, 2012)
Purpose – The purpose of this study is to investigate the impact of perceived organizational support (POS), perceived supervisor support (PSS) and intra-organizational network resources on the turnover intentions of the Chinese employees of multinational enterprises. Design/methodology/approach – The study utilized structured equation modeling to analyze survey data from 437 Chinese employees of five multinational enterprises operating in the Chinese service sector. Findings – The study found that POS was positively related to affective organizational commitment, which in turn was negatively related to turnover intentions. A direct relationship was revealed between PSS and turnover intentions, as well as a mediated relationship through POS. In contrast, the relationship between intra-organizational network resources and turnover intentions was fully mediated through POS. Research limitations/implications – The cross sectional design is a limitation of the study. Another limitation regards the generalisability of the findings outside the specific research context. Future research should be extended to different geographical and organizational settings.Practical implications – In order to promote employee retention, multinational enterprises operating in China could start by carefully targeting visible support on offer to their employees. Improving supervisor support is a relatively inexpensive and practical measure compared to the costly alternatives such as improving employee compensation, training and career development. Organizations should also consider improving co-worker support schemes in the workplace which enable individuals to build up their network resources. Originality/value – The study provided evidence for both a direct relationship between PSS and turnover intentions and a mediated one via POS, confirming the generalisability of previous findings to the Chinese context. In addition it made an original contribution by establishing that POS fully, rather than partially mediated the relationship between intra-organizational network resources and turnover intentions. This suggests that Chinese employees attribute instrumental and expressive support from others in the organization as coming from the organization itself.